Influence of temperature on the strain rate sensitivity and deformation mechanisms of nanotwinned Cu. (September 2018) - Yang, L.W.; Wang, C.Y.; Monclús, M.A.; Lu, L.; Molina-Aldareguía, J.M.; Llorca, J.
Abstract: The mechanical behavior of nanotwinned Cu was studied through indentation creep and constant strain rate indentation tests from 25 °C to 200 °C. The results showed an enhanced strain rate sensitivity of nanotwinned Cu with temperature, which was higher than that found in coarse-grained Cu. Transmission electron microscopy revealed the same deformation mechanism in the whole temperature range: confined dislocation slip between coherent twin boundaries and formation of dislocation pile-ups at the coherent twin boundaries. The mechanisms responsible for large increase in strain rate sensitivity of nanotwinned Cu with temperature were discussed to the light of experimental observations. Graphical abstract: Unlabelled Image